Early Arcus - An Important Alert - Rona, Zoltan; Paige, Ned (Canadian Journal of Optometry, 1983)
Soon after being fitted with contact lenses, a 26-year old male who had presented an arcus, developed intolerance to the lenses. A subsequent medical examination which included biochemical tests, confirmed the condition of arcus juvenilis. Comments on the management of such cases are offered.